Influence of ag-doped on magnetic and electrical transport properties in Pr0.75Na0.25MnO3 manganites - Khairulzaman, Nurul Nasuha (2019)
The manganites compound in which composed of the manganese oxide are attract considerable attention among researcher due to their electrical and magnetic properties at lower temperature. However, most of the doping does not totally induce the ferromagnetic-metallic (FMM) state probably due to dopant level. As such, the influence of ion doped on host composition need to be further investigated. In this study, the monovalent doped Pr0.75Na0.25-yAgyMnO3 (y = 0 – 0.10) manganites was prepared by solid-state reaction method. All samples have been characterized using the X-ray diffraction (XRD) and scanning electron microscope (SEM) as well as DC electrical resistivity and AC susceptibility measurement to clarify the influence of Ag-doped on monovalent doped manganites. XRD analysis revealed all samples consists of essentially single phase and crystallized in an orthorhombic structure with space group Pnma. SEM images of Pr0.75Na0.25-yAgyMnO3 compound shows the successful substitution of Ag+ ions with the enhancement of the grains boundaries and sizes as well as the compaction of particles. On the other hand, susceptibility and resistivity measurements showed that the y = 0 sample exhibits anti-ferromagnetic insulating behaviour with Néel temperature, TN ~ 125 K. Interestingly, the FMM transition was observed for y = 0.05 with the metal insulator transition temperature, TMI ~ 110 K and Curie temperature, TC ~ 123 K. However, increasing of Ag-doped up to y = 0.10 showed an insulating behaviour and paramagnetic-ferromagnetic transition with TC around 126 K. Apart from that, the resistivity behaviour at temperature region above TMI for y = 0  0.10 was found to fit well with the variable range hopping model (VRH) with the increasing of hopping and activation energy as the Ag concentration increased. While for the metallic region which is below the TMI, the resistivity data of y = 0.05 was fitted well with the combination of domain/grain boundary, electron-electron and electron-magnon scattering.